THE IMPACT OF THE U-VISA ON STOPPING VIOLENCE AGAINST IMMIGRANT WOMEN IN THE USA. (7th October 2012) - Olson, L; Kamimura, A; Gonzalez, M
Abstract : Background: The Violence Against Women Act created the U-visa to strengthen the ability of law enforcement to prosecute cases of domestic violence and other violent crimes committed against immigrants who are abused by a boyfriend or person who is not a spouse or who is not a US citizens or permanent resident. Objective: Understand the development of the relationship and the history and patterns of abuse. Methods: Qualitative analysis of 48 U-Visa affidavits. The affidavit, one element of the evidence for U-Visa applications is the chronological story told in the immigrants' own words of her relationship with the perpetrator and the abuse. Results: Most applicants met and partnered with perpetrator in native country. Relationships often started out with perpetrator being 'kind and sweet' but emotional abuse, in the form of threats to report applicant to immigration or keep custody of children and withholding of finances along with severe physical and sexual abuse occurred within a year of moving to USA. Contact with the police was usually initiated by the victim. Barriers to contacting police included fear of deportation, dependency on abuser, and loss of children. Shelters and victim advocates were the main source of help for women. Significance: While the U-visa gives the immigrant applicant the possibility of lawful permanent residence, to qualify, the immigrant must overcome fears of deportation and cooperate with the police. The affidavit provides a picture of how the abuse started and offers ideas for prevention and intervention.